Supplement use and behaviors of athletes affiliated with an Australian state-based sports institute - Waller, M. C.; Kerr, D. A.; Binnie, M. J.; Eaton, E.; Wood, C.; Stenvers, T.; Gucciardi, D. F.; Goodman, C.; Ducker, K. J. (International Journal of Sport Nutrition and Exercise Metabolism, 2019)
The authors aimed to update knowledge of the use of supplements among Australian athletes at a state-based sports institute. The authors conducted a cross-sectional survey using an online questionnaire to assess the influence of age, sports category, and scholarship category on supplement use. Of 94 completed questionnaires, 82 (87%) indicated supplements in the previous 12 months (mean = 4.9 ± 3.3). No significant difference in supplement usage rate was identified when considering age, scholarship category, or sport category. The most frequently used supplements were sports drinks (70%), caffeine (48%), protein powder (42%), and sports bars (42%). Recovery (63%), health maintenance (59%), and improved energy (50%) were the most frequently reported rationale to use supplements. Allied health professionals and credible online resources were the predominant sources of influence regarding use. However, athletes from lower scholarship categories were more likely to have social media, parents, and siblings influence usage, and age was inversely related to increased influence from parents, social media, physicians not associated with the institute, the Internet, and siblings. Older athletes and those on higher scholarships were more likely to source supplements from training facilities and sports nutrition staff outside of the institute or direct from a supplier, whereas those on lower scholarships tended to rely more on family and friends for their supplements. Findings from this study show a high prevalence of supplement use and are the first to show an influence of social media, particularly in younger athletes. Opportunities exist to optimize how athletes are informed regarding supplement use and organizational and supplement policy.